Interrelated aldosterone and parathyroid hormone mutually modify cardiovascular mortality risk - Tomaschitz, Andreas; Grammer, Tanja B.; Ritz, Eberhard; Kleber, Marcus E.; März, Winfried (International journal of cardiology, 2015)
Inappropriate aldosterone and parathyroid hormone (PTH) secretion is associated with increased cardiovascular risk. Accumulating evidence suggests bidirectional interplay between aldosterone and PTH. We evaluated the cross-sectional relationship between plasma aldosterone concentration (PAC), aldosterone to renin ratio (ARR) and PTH and subsequently tested whether the interaction between PAC and PTH modified the risk of cardiovascular death. PAC [78.0 (48.0-123.0) pg/mL], ARR [6.4 (2.9-12.9) pg/mL/pg/mL] and PTH concentration [median: 29.0 (22.0-40.0) pg/mL] were measured in 3074 patients (mean age: 62.5±10.6years; 30.3% women) referred to coronary angiography in a tertiary care center in Southwest Germany. Using multiple linear regression analysis, PAC and ARR emerged as an independent predictor of higher PTH concentrations (β=0.12 and 0.21, P<0.001 for both) irrespective of intake of antihypertensive treatment, 25(OH)D, kidney function, serum calcium, phosphate, magnesium, cortisol, NT-pro-BNP, soluble α-klotho and FGF-23 concentration. After a median follow-up of 9.9years, 512 (16.7%) participants had died due to fatal cardiovascular events. Multivariate Cox proportional hazard analysis revealed that both PAC and PTH were independently associated with cardiovascular mortality, with a potential synergistic interaction (P=0.028). PAC and PTH are exclusively associated with cardiovascular death in subjects with PTH and PAC concentrations above the median, respectively (PAC: HR per log SD: 1.14; 95% CI 1.02-1.29; P=0.026; PTH: HR per log SD: 1.18; 95% CI 1.02-1.37; P=0.031). Higher PAC and ARR were independently associated with PTH. PAC was independently related to incident cardiovascular mortality exclusively in patients with elevated PTH and vice versa.